Fikih Kiri: Revitalisasi Usul al-Fiqh untuk Revolusi Sosial - Nugroho, Anjar (Al-Jamiah Research Centre, 2005)
Classical fiqh, which is based on classical Usul al-Fiqh, has often been considered out of date and no longer has its effectiveness at handling new problems. The article is a study critically addressed to the classical theory of Usul al-fiqh, which is commonly accused as a factor that made fiqh static and has nothing to do with reality. The writer proposes, then, how to develop a new model of fiqh that is more sensitive to the real issues of society, left fiqh. The left fiqh is fiqh that takes side with oppressed, impoverished people (mustadâafin) and demands criticism to a hegemonic power. This is an antithesis to mainstream fiqh, which tends to be used to protect people with the power. It is expected that left fiqh may colourize both the process and the result of ijtihad of Muslim scholars. Fiqh that is not sensitive to human problems will merely legitimate illegal collusion. If fiqh does not insist on handling and overcoming human problems, it will experience two problems: first, fiqh will indulge in its settled condition as a well established doctrine and will be always considered unnecessary. Second, fiqh will progressively narrow its role merely focused on ritual and make its self powerless at solving daily human problems.